Nilai Religius dalam Tradisi Baritan di Desa Wates Kabupaten Blitar - Shova Afkaryna; Bagus Wahyu Setyawan (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Indonesia, with its abundant wealth of traditions and cultures, stands out as a country renowned for its diverse cultural heritage. One unique tradition still firmly held by its people is Baritan. Baritan is a customary practice that continues to be observed by the residents of Desa Wates, located in the Wates sub-district of Blitar Regency. This tradition holds its uniqueness as it is usually conducted when the rainy season arrives, serving as a symbol of gratitude to God for the blessing of rain, which is crucial for agriculture and plant growth, and marking the beginning of a new planting season. The research method employed in this article is qualitative, allowing researchers to delve deeper into the cultural aspects and social meanings of the Baritan tradition. Despite Indonesia's rapid advancements in technology and modernization, particularly with the progress in science and technology (IPTEK), there remain challenges in preserving the sustainability of traditional customs such as Baritan. The younger generation, especially in Desa Wates, Blitar Regency, have not fully grasped and appreciated the religious values embedded in the Baritan tradition. Many of them participate in the tradition without understanding its deeper meanings and significance. Therefore, this study aims to delve deeper into the implementation stages of the Baritan tradition and the religious values contained within it. These religious values encompass aspects of belief (aqidah), Islamic law (syari'ah), and morality (akhlak), which form the main foundation in the implementation of the Baritan tradition.